ZnCo2O4 nanosheets as an efficient electrochemical sensing platform for determination of paracetamol - Nguyen Ngoc, Huyen; Ngo Xuan, Dinh; Vu Ngoc, Phan; Le Minh, Tung; Pham Duc, Thang; Le Anh, Tuan (Vietnam Journal of Science and Technology, 2025)
ZnCo2O4 nanosheets (ZCO) were synthesized by a simple method using microwave-assisted hydrothermal technique. X-ray diffraction (XRD), UV-vis spectroscopy (UV-vis), and scanning electron microscope (SEM) methods were used to study the structural characteristics, morphologies, and sizes of the synthesized materials. A ZnCo2O4 nanosheet-modified screen-printed electrode (ZCO/SPE) acted as an effective electrochemical sensor for determining paracetamol (PCM). The PCM oxidation peak current response for ZCO/SPE was 37.7 percent higher than that of bare SPE. Under optimized conditions, the ZnCo2O4-based electrochemical sensor exhibited a linear response from 0.5 to 100 µM with a high electrochemical sensitivity of 4.27 µA µM-1cm-2 and a limit of detection (LOD) of 0.19 µM. In addition, the as-synthesized electrochemical sensors had high anti-interference ability and excellent stability for the determination of PCM.